2020
DOI: 10.2106/jbjs.19.00874
|View full text |Cite
|
Sign up to set email alerts
|

Implant Survival of 6,080 Tritanium Cups in Primary Total Hip Arthroplasty

Abstract: Background: To enhance osseointegration in total hip arthroplasty (THA), ultraporous or highly porous-coated cups were introduced. Implant survival data on these new devices have been scarce. The aim of our study was to assess the survivorship of ultraporous Tritanium cups (Stryker) in a population-based register study. Methods: In this study, we collected data on 6,080 primary THAs using a Tritanium cup and 25,670 THAs using a conventional cup (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Many studies have suggested that these factors can have an influence on a higher risk of overall revision, like a specific cup type, a lower age at the moment of surgery and female gender. [32][33][34][35] Although the higher incidence of revision in CoC was still significant after correction for these confounders in our study, it shows that the aetiology of early revision is multi-factorial. Focusing on aseptic loosening, in older patients, due to the reduced quality and density of the subchondral trabecular bone, in which the cup is inserted after reaming, there may be an increase in its elasticity.…”
Section: Discussioncontrasting
confidence: 51%
“…Many studies have suggested that these factors can have an influence on a higher risk of overall revision, like a specific cup type, a lower age at the moment of surgery and female gender. [32][33][34][35] Although the higher incidence of revision in CoC was still significant after correction for these confounders in our study, it shows that the aetiology of early revision is multi-factorial. Focusing on aseptic loosening, in older patients, due to the reduced quality and density of the subchondral trabecular bone, in which the cup is inserted after reaming, there may be an increase in its elasticity.…”
Section: Discussioncontrasting
confidence: 51%
“…Comparing the two groups with regard to revision for any reason, the 5-year Kaplan–Meier survivorship of the Tritanium cup group (94.7%) was significantly inferior to that of the conventional titanium alloy cup group (96.0%). In the Cox regression analysis, there was an increased risk of revision for any reason in the Tritanium cup group compared with the conventional titanium alloy cup group at >4 years (hazard ratio, 3.12) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular screws favor primary stability and ensure better cup osseointegration (56), and trabecular metal acetabular cups benefit long-term osseointegration (57). Moreover, the implant coating type, porous covering extent, and the surgeon's expertise may also affect the AL risk (58,59,60,61). Additionally, numerous diseases such as diabetes mellitus, rheumatoid arthritis, sickle cell or Parkinson's disease (11,13,14,62), previous surgical operations such as spinal fusion or hip arthroscopy (63), and various drugs such as statins, beta-blockers and opioids have been implicated to the AL development (15, 16, 64).…”
Section: Discussionmentioning
confidence: 99%